2011
DOI: 10.5301/jabb.2011.8565
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of implant-tooth supported prostheses: effects of mesiodistal implant angulation and mode of prosthesis connection

Abstract: This investigation suggests that mesiodistal tilting of implants may have a biomechanical effect in tooth-implant supported prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…More failures of this treatment modality were associated with maxillary bone, short implants, tilted implants, poor bone quality, and using endodontically treated teeth as abutments [14, 20, 28, 50, 51, 81, 82]. Block et al [51] reported the removal of 5 abutment teeth that were endodontically treated and connected to implants after being fractured at the interface of the post within the tooth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More failures of this treatment modality were associated with maxillary bone, short implants, tilted implants, poor bone quality, and using endodontically treated teeth as abutments [14, 20, 28, 50, 51, 81, 82]. Block et al [51] reported the removal of 5 abutment teeth that were endodontically treated and connected to implants after being fractured at the interface of the post within the tooth.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a long term follow-up clinical study of implant and tooth supported prostheses reported more biological complications and failures when abutment teeth were endodontically treated or had reduced bone attachment levels (i.e., affected by periodontal disease) [15]. Also, tilting the implants has biomechanical effects including increased peri-implant strains within implant-tooth supported prostheses during torque-tightening and under load [81]. …”
Section: Resultsmentioning
confidence: 99%
“…Implant therapy is a common treatment to replace missing teeth. When implants were first introduced, machined implants were the standard [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Since then, various types of implants with different surface properties have been developed with the objective of earlier attainment of osseointegration.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Bavbek et al . [ 5 ] reported that peri-implant stress increased with the use of a mesiodistal implant/tooth-supported connected prosthesis. Moreover, Zarone et al .…”
Section: Introductionmentioning
confidence: 99%
“…eoretical problems are thought under the light of the clinical cases and help avoiding the complications related to the mobility of teeth-implant [20]. For this purpose, it will be better to consider the most common complication which is bone loss around the implant/teeth and intrusion of natural teeth.…”
Section: Advantages and Potential Problems In Connection Of Natural Tmentioning
confidence: 99%